HUBUNGAN PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL DENGAN TINGKAT KEPATUHAN ANTENATAL CARE DI PUSKESMAS ANDALAS KOTA PADANG TAHUN 2020 - Tia Reza,; Rayhan Radisa,; Nurwiyeni, Nurwiyeni; Prima Adelin,; Febianne Eldrian, (Nusantara Hasana Journal, 2024)
Anaemia is a condition where there is a decrease in haemoglobin, hematocrit, or erythrocytes count. This condition makes them unable to fulfil their function in providing oxygen to the tissues. Indonesia has a high prevalence of anaemia among pregnant women. Based on RISKESDAS, the number of pregnant women with anaemia has increased every year. Antenatal Care (ANC) services as government policies and strategies can be used as early screening for high-risk pregnancy conditions. This service is very important for pregnant women because one of the minimum standards for ANC services is the administration of Fe tablets. Pregnant women should consume at least 90 tablets during pregnancy. However, some pregnant women in Indonesia do not know the importance of ANC visits and have not made ANC a top priority, especially in remote or rural areas with minimal health facilities. This study is an unpaired categorical analytic study with a cross-sectional approach. Data collection in this study used secondary data derived from medical records. The results of this study's bivariate analysis indicate a relationship between increased haemoglobin levels in pregnant women and the level of antenatal care compliance at the Andalas Community Health Center, Padang City, in 2020. Based on the results of this study, it can be concluded that pregnant women who experience increased haemoglobin levels mostly have a high level of ANC compliance. However, not all pregnant women who presented at ANC experience an increase in haemoglobin levels. This change is influenced by the level of compliance of pregnant women in consuming Fe tablets. Furthermore, it is necessary to educate pregnant women about the benefits of consuming Fe tablets during pregnancy during ANC visits.